Mitochondrial Function in an In Vitro Model of Skeletal Muscle of Patients With Protracted Critical Illness and Intensive Care Unit-Acquired Weakness - Jiroutková, Kateřina; Krajčová, Adéla; Žiak, Jakub; Fric, Michal; Gojda, Jan; Džupa, Valér; Kalous, Martin; Tůmová, Jana; Trnka, Jan; Duška, František (JPEN. Journal of parenteral and enteral nutrition, 2017)
BACKGROUND: Functional mitochondria in skeletal muscle of patients with protracted critical illness and intensive care unit-acquired weakness are depleted, but remaining mitochondria have increased functional capacities of respiratory complexes II and III. This can be an adaptation to relative abundancy of fatty acid over glucose caused by insulin resistance. We hypothesized that the capacity of muscle mitochondria to oxidize fatty acid is increased in protracted critical illness. METHODS: We assessed fatty acid oxidation (FAO) and mitochondrial functional indices in vitro by using extracellular flux analysis in cultured myotubes obtained by isolating and culturing satellite cells from vastus lateralis muscle biopsy samples from patients with ICU-acquired weakness (n = 6) and age-matched healthy controls (n = 7). Bioenergetic measurements were performed at baseline and after 6 days of exposure to free fatty acids (FFAs). RESULTS: Mitochondrial density in myotubes from ICU patients was 69% of healthy controls ( P = .051). After adjustment to mitochondrial content, there were no differences in adenosine triphosphate (ATP) synthesis or the capacity and coupling of the respiratory chain. FAO capacity in ICU patients was 157% of FAO capacity in controls ( P = .015). In myotubes of ICU patients, unlike healthy controls, the exposure to FFA significantly ( P = .009) increased maximum respiratory chain capacity. CONCLUSION: In an in vitro model of skeletal muscle of patients with protracted critical illness, we have shown signs of adaptation to increased FAO. Even in the presence of glucose and insulin, elevation of FFAs in the extracellular environment increased maximal capacity of the respiratory chain.
Keywords: senioři; Quadriceps Muscle; Electron Transport; Intensive Care Units; Fatty Acids, Nonesterified; krevní glukóza; Mitochondria, Muscle; fyziologická adaptace; svalová slabost; inzulin; Middle Aged; human skeletal muscle; mužské pohlaví; Insulin; Energy Metabolism; kosterní svalová vlákna; Muscle, Skeletal; protracted critical illness; čtyřhlavý sval stehenní; Lipolysis; transport elektronů; energetický metabolismus; Blood Glucose; fatty acid oxidation; ženské pohlaví; Muscle Fibers, Skeletal; mitochondrial function; Humans; kritický stav; svalové mitochondrie; respirační komplex II; kosterní svaly; Muscle Weakness; jednotky intenzivní péče; extracellular flux analysis; lidé středního věku; Electron Transport Complex II; ICU-acquired weakness; kyseliny mastné neesterifikované; inzulinová rezistence; Critical Illness; Female; Aged; Insulin Resistance; lipolýza; lidé; Male; Adaptation, Physiological